Citizen‐Suspect: Navigating Surveillance and Policing in Urban Kenya. Issue 4 (17th August 2021) - Al‐Bulushi, Samar
ABSTRACT: This article privileges the grounded geographies of the war on terror, focusing on those who grapple with its everyday policing powers. Informed by ethnographic research in the cities of Nairobi and Mombasa, I explore how Kenyan Muslim activists experience and make sense of the networked assemblages of police power that transform urban spaces into "gray zones" that fall within the ambiguous spectrum between war and peace. As US‐trained Kenyan police employ military tactics of tracking and targeting potential terror suspects in quotidian urban spaces, they rely on "pop‐up" interventions such as abductions, house raids, and makeshift checkpoints—flexible maneuvers designed to match the amorphousness of the so‐called enemy. I introduce the term citizen‐suspect to shed light on actually existing citizenship in the urban gray zone. Citizen‐suspects contend not simply with the fear and paranoia that come with subjection to surveillance and suspicion but with the knowledge that is needed to navigate the shape‐shifting geographies of transnational policing. RESUMEN: Este artículo privilegia las geografías basadas en la guerra contra el terror, enfocándose en aquellos que luchan a diario con sus poderes policiales. Informada por la investigación etnográfica en las ciudades de Nairobi y Mombasa, exploro cómo activistas musulmanes kenianos experimentan y entienden los ensamblajes en la red del poder policial que transforma los espacios urbanos en "zonas grises" que encajan dentro del espectro ambiguo entre la guerra y la paz. En la medida en que la policía keniana entrenada por los Estados Unidos utiliza tácticas militares de seguimiento y enfoque en sospechosos potenciales de terrorismo en espacios urbanos cotidianos, ellos dependen de intervenciones "emergentes" tales como abducciones, allanamientos a residencias y puntos de control temporales –maniobras flexibles diseñadas para coincidir con el carácter amorfo del así llamado enemigo–. Introduzco el término ciudadano‐sospechoso para iluminar la ciudadanía existente en realidad en la zona urbana gris. Los ciudadanos‐sospechosos se enfrentan no simplemente al miedo y la paranoia que vienen con ser sujetos a la vigilancia y la sospecha sino al conocimiento que es necesario para navegar las geografías cambiantes de la forma del monitoreo transnacional. [ militarismo, monitoreo, vigilancia, ciudadanía, ciudades, África ]